Pengetahuan Ibu Tentang Teknik Memijat pada Bayi Usia 0-12 Bulan (Studi di Desa Bulurejo Kec. Diwek Kab. Jombang) - siti muniroh; Kurniawati Kurniawati (Jurnal EDUNursing, 2017)
Abstract Infant massage is the oldest and most popular touch therapy known to man. Role in ruralcommunities is still held by the midwife. Lack of knowledge of mothers on infant massagetechniques, could result in the mother can not properly massage their infants would likely occur a result of unwanted things that could be fatal for infants.The purpose of this study was determine maternal knowledge about massage techniques on infants aged 0-12 months.The methodused is descriptive survey approach. Samples taken in this study were mothers who had infantaged 0-12 months in the Village District Bulurejo Diwek Jombang District, in a way probabililisampling with cluster sampling technique, number of population is 116 by the number of samplused 89 respondents who carried out the month June 2012. The instrument used was questionnaire. From the results showed 42.7% knowledgeable enough about the massatechniques on infants aged 0-12 months, 34.8% and 22.5% knowledgeable both lesknowledgeable. It is expected that the mothers further enhance knowledge of massage techniqueon infants aged 0-12 months with more consultation with local health workers, following tcounseling's and find information in various media such as books, internet, television, radio, andso forth, so the mother can increase knowledge.  Key words: Knowledge Capital, Technical Massaging the Baby Ages 0-12 Months